Codon-dependent conformational change of elongation factor Tu preceding GTP hydrolysis on the ribosome. - Rodnina, M V (1995)
The mechanisms by which elongation factor Tu (EF-Tu) promotes the binding of aminoacyl-tRNA to the A site of the ribosome and, in particular, how GTP hydrolysis by EF-Tu is triggered on the ribosome, are not understood. We report steady-state and time-resolved fluorescence measurements, performed in the Escherichia coli system, in which the interaction of the complex EF-Tu.GTP.Phe-tRNAPhe with the ribosomal A site is monitored by the fluorescence changes of either mant-dGTP [3'-O-(N-methylanthraniloyl)-2-deoxyguanosine triphosphate], replacing GTP in the complex, or of wybutine in the anticodon loop of the tRNA. Additionally, GTP hydrolysis is measured by the quench-flow technique. We find that codon-anticodon interaction induces a rapid rearrangement within the G domain of EF-Tu around the bound nucleotide, which is followed by GTP hydrolysis at an approximately 1.5-fold lower rate. In the presence of kirromycin, the activated conformation of EF-Tu appears to be frozen. The steps following GTP hydrolysis--the switch of EF-Tu to the GDP-bound conformation, the release of aminoacyl-tRNA from EF-Tu to the A site, and the dissociation of EF-Tu-GDP from the ribosome--which are altogether suppressed by kirromycin, are not distinguished kinetically. The results suggest that codon recognition by the ternary complex on the ribosome initiates a series of structural rearrangements resulting in a conformational change of EF-Tu, possibly involving the effector region, which, in turn, triggers GTP hydrolysis.